2014
DOI: 10.3168/jds.2013-7785
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of clinical mastitis, cystic ovaries, and lameness with milk yield and somatic cell score in first-lactation Canadian Holsteins

Abstract: The objective of this study was to investigate the genetic relationships of the 3 most frequently reported dairy cattle diseases (clinical mastitis, cystic ovaries, and lameness) with test-day milk yield and somatic cell score (SCS) in first-lactation Canadian Holstein cows using random regression models. Health data recorded by producers were available from the National Dairy Cattle Health System in Canada. Disease traits were defined as binary traits (0=healthy, 1=affected) based on whether or not the cow ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 25 publications
4
42
0
3
Order By: Relevance
“…Also, Koeck et al. () found that cows with a high EBV for milk yield were more susceptible to OC, and estimated a genetic correlation of 0.26 between daily milk yield and OC. Garnsworthy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Koeck et al. () found that cows with a high EBV for milk yield were more susceptible to OC, and estimated a genetic correlation of 0.26 between daily milk yield and OC. Garnsworthy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dechow and Goodling (2008) reported that early culling was a reliable indicator of poor cow health. Several studies (Simianer et al, 1991;Rauw et al, 1998;Koeck et al, 2013b) have reported that an antagonistic relationship exists between milk production and disease resistance. Beaudeau et al (2000) reported that metabolic disorders have effects on milk production, reproductive performance, and culling.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop feasible total merit indices and to introduce new selection traits in the genetic improvement programmes, there is a need for up-to-date information on a wide range of relevant traits that have economical and animal welfare implications [1]. The main drawback on introducing functional traits into breeding programmes is the general low genetic additive variance, with heritability estimates of 0.02 to 0.09 for clinical mastitis [3], 0.01 to 0.07 for fertility-related diseases [4] and 0.02 to 0.04 for lameness [5]. …”
Section: Introductionmentioning
confidence: 99%